From south to north: class and neighborhood in la Ultra Morada - Rodríguez Aguilar, Onésimo Gerardo (2014)
This paper explores some dynamics developed by La Ultra Morada (group amateur organized mostly younger supporters of Deportivo Saprissa, created in April 1995), which refer to the organization, structuring it. Also, two other important dimensions in this youth group, namely, the condition of neighborhood and some class specificity. Permeated by hedonic games and playful, the young members and do not give up their criticism and reflection of their daily, on the contrary, the references to the neighborhood and the differentiated economic position, outlined the construction of reflexive subjectivities from ecstasy positions and vice versa. Finally, it is important to note that the field which follows this article, was conducted from 2003 to 2006 (as part of a research thesis form entitled: “Between songs and stands: the construction of a youth group of Costa Rican football field’s. The case of La Ultra Morada”), which could mean that many of the dynamics of the youth group and reflected described here are either re meaning, taken nuances differentiated.